PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU), DANA ALOKASI KHUSUS (DAK), DANA BAGI HASIL (DBH) DAN SISA LEBIH PEMBIAYAAN ANGGARAN (SILPA) TERHADAP BELANJA MODAL DI PROVINSI D.I. YOGYAKARTA TAHUN 2013-2020 - Rini Marliana; Agung Slamet Prasetyo; Prafidhya Dwi Yulianto (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This research was conducted to prove the effect of Regional Original Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), Profit Sharing Fund (DBH), and Remaining Budget Financing (SILPA) on Capital Expenditures in Regional ProvincesYogyakarta Special Year 2013-2020. This research method is quantitative by conducting multiple linear regression analysis between the variables of Regional Original Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), Profit Sharing Fund (DBH) and Over Budget Financing (SILPA) on Capital Expenditures. The population in this study is the City/Regency in the Province of the Special Region of Yogyakarta in 2013-2020. The sample in this study was determined by purposive sampling. .This study concludes that Regional Original Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK) have a significant positive effect on Capital Expenditures, while Revenue Sharing Funds (DBH) and Over Budget Financing (SILPA)does not have a significant positive effect on Capital Expenditures.This shows that Regional Original Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), Revenue Sharing Fund (DBH) and Budget Financing Excess Remaining (SILPA) simultaneously affect Capital Expenditure.